If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (275)(373 + -1x)(0.444) = (100)(x + -295)(4.184) Reorder the terms for easier multiplication: 275 * 0.444(373 + -1x) = (100)(x + -295)(4.184) Multiply 275 * 0.444 122.1(373 + -1x) = (100)(x + -295)(4.184) (373 * 122.1 + -1x * 122.1) = (100)(x + -295)(4.184) (45543.3 + -122.1x) = (100)(x + -295)(4.184) Reorder the terms: 45543.3 + -122.1x = 100(-295 + x)(4.184) Reorder the terms for easier multiplication: 45543.3 + -122.1x = 100 * 4.184(-295 + x) Multiply 100 * 4.184 45543.3 + -122.1x = 418.4(-295 + x) 45543.3 + -122.1x = (-295 * 418.4 + x * 418.4) 45543.3 + -122.1x = (-123428 + 418.4x) Solving 45543.3 + -122.1x = -123428 + 418.4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-418.4x' to each side of the equation. 45543.3 + -122.1x + -418.4x = -123428 + 418.4x + -418.4x Combine like terms: -122.1x + -418.4x = -540.5x 45543.3 + -540.5x = -123428 + 418.4x + -418.4x Combine like terms: 418.4x + -418.4x = 0.0 45543.3 + -540.5x = -123428 + 0.0 45543.3 + -540.5x = -123428 Add '-45543.3' to each side of the equation. 45543.3 + -45543.3 + -540.5x = -123428 + -45543.3 Combine like terms: 45543.3 + -45543.3 = 0.0 0.0 + -540.5x = -123428 + -45543.3 -540.5x = -123428 + -45543.3 Combine like terms: -123428 + -45543.3 = -168971.3 -540.5x = -168971.3 Divide each side by '-540.5'. x = 312.6203515 Simplifying x = 312.6203515
| 3y+10=82 | | -1/7y^7*5/8y^2 | | 5m+25=-65 | | 2x=6-y | | 3.7x-4=2.7x | | (6x-3)(-2x-14)= | | (-6x+3)(2x-14)= | | (-3x+9)(4x-2)= | | 6*9-9y=-54 | | c^2=2c+35 | | 9.7/5.9 | | y^2+100=20y | | (x+1)(x-1)(x-8)=0 | | 4z=18-26 | | (6x^3-1x^2+1)/(2x+1) | | (6x-54)/5=-3x | | 30=6r-24+3t | | 7-(-5)+4-(-3)= | | 12=-2m | | -x-(1/7)=x+(1/6)+(2/7) | | 1/6x^2=48 | | 4w+13=61 | | x+2(x-4)=100 | | 1/3x^2=48 | | (275)(x-373)(.444)=(100)(x-295)(4.184) | | 1/3x^2=54 | | Y=3/2*0-6 | | -.25x+6x-2=20 | | 8/x+8=7/x-4 | | 7t^2+3=10t | | 0.18(y-8)+0.14y=0.16y-0.05(60) | | (3/9)+(x/3)=7/9 |